Evaluation of Parental Awareness, Attitudes, and Perceptions Regarding Autism Spectrum Disorders in Kuwait - Al Aqel, Abdullah (2026)
Purpose: This cross-sectional study in Kuwait aims to evaluate parents’ knowledge, attitudes, and beliefs regarding autism spectrum disorders (ASD), with a specific focus on the mediating influence of expertise. Autism spectrum disorder (ASD) it’s a multifaceted neurodevelopmental disease that impacts communication and social interaction. Timely diagnosis and management are essential for enhancing outcomes. Nevertheless, numerous regions, including Kuwait, experience a deficiency in parental knowledge, potentially obstructing early intervention. This study examines the impact of stigma and social awareness activities on parental comprehension, analyzing how these elements influence attitudes and views regarding ASD. Methods: The study employs a structured questionnaire distributed to 500 parents to assess their understanding of autism, exposure to awareness initiatives, and views of stigma. The study was utilizing mediation analysis to investigate how knowledge and perception mediate the interactions among stigma, social awareness initiatives, and parental attitudes. Results: Social awareness initiatives significantly influenced perception (β = 0.684, p < 0.001) and attitude (β = 0.218, p = 0.002), underscoring their role in shaping positive parental views toward ASD. Stigma had a substantial negative impact on attitude (β = -0.459, p < 0.001). However, stigma did not significantly affect perception (β = -0.037, p = 0.338), and the relationship between perception and attitude (β = 0.100, p = 0.132). These findings highlight the critical role of awareness campaigns in reducing stigma and fostering positive attitudes. Conclusion: This study seeks to enhance the understanding and assistance for individuals with autism and Kuwait.